11x+13=11x+13

Simple and best practice solution for 11x+13=11x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+13=11x+13 equation:


Simplifying
11x + 13 = 11x + 13

Reorder the terms:
13 + 11x = 11x + 13

Reorder the terms:
13 + 11x = 13 + 11x

Add '-13' to each side of the equation.
13 + -13 + 11x = 13 + -13 + 11x

Combine like terms: 13 + -13 = 0
0 + 11x = 13 + -13 + 11x
11x = 13 + -13 + 11x

Combine like terms: 13 + -13 = 0
11x = 0 + 11x
11x = 11x

Add '-11x' to each side of the equation.
11x + -11x = 11x + -11x

Combine like terms: 11x + -11x = 0
0 = 11x + -11x

Combine like terms: 11x + -11x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5x^2+23x+10=0 | | 2h^2-11h-21=0 | | x+0.06x=9999 | | .375t^2+6t-120=0 | | x^3+3.75x^2+4x+1.5=0 | | 12x-3+75=180 | | (6u-y)+4(-5y-u)= | | 4x^2-20x+25y^2= | | f(-2)=5 | | 20x+11x-6=180 | | X-6=-8x+12 | | 54+x=50 | | 5a+2=3a+9 | | (2x^2)+6x-5=0 | | z^2-2z+9=0 | | 50=x+54 | | 55=9x+1 | | -282-(1017)=x | | 12(2x-3)=3(8x+9) | | 6x^2+9y^2=32 | | 20x+39x+3=180 | | 11z+5=4z-5 | | 10t+6=-14-2t | | 11x+7+17x+5=180 | | 5+3m-4=7m+11-2 | | -42=5x-27 | | 12x+2=5x | | x^3+2x^2-1x-2=0 | | 5+3(x-4)=2(x+1) | | x^3+2x^2-11x-2=0 | | .16*225= | | .12*120= |

Equations solver categories